Kata Kunci: Kenaikan Laba, Return Saham, Kenaikan Dividen. - Nur Aisyah, Anjali; Sri Suwarsi; Firman Shakti Firdaus (Bandung Conference Series: Business and Management, 2023)
Abstract. In the company work life balance is a term for balancing personal life and work. The balance that occurs between each employee is viewed from work life and personal life. Which if every millennial generation employee cannot balance his role, it can lead to the intention to quit his job. Millennial generation employees who cannot balance their time and dual roles can cause turnover intention in the CTBC Bank Agency company. This study aims to (i) analyze the Work Life Balance of Millennial Generation employees at the CTBC Bank Agency office (ii) to determine the Turnover Intention of Millennial Generation employees at the CTBC Bank Agency office (iii) to determine and analyze the effect of Work Life Balance on Turnover Intention of Millennial Generation Employees at the CTBC Bank Agency office in Bandung City. In this research, researchers involved 30 millennial generation employees who became research samples. In exploring data, researchers use primary data which includes questionnaires, interviews, observations and also secondary data including documents, books using the IBM SPSS 25 program as data analysis. The method used in this research is quantitative with a descriptive verification approach. The results of this research are (i) Work life balance of millennial generation employees of the CTBC Bank Agency has been assessed as good, meaning that millennial generation employees have a good ability to balance work demands with personal and family needs (ii) Turnover intention of millennial generation employees in the high category means that millennial generation employees are able to balance the level of work so as to reduce the desire and reduce thoughts of leaving the company so that it is considered good (iii) Work life balance has a significant negative effect on Turnover intention of millennial generation employees. The results obtained are that the higher the work life balance carried out, the lower the level of turnover intention. Conversely, the lower the work life balance, the higher the turnover intention level. Abstrak. Didalam perusahaan work life balance merupakan suatu istilah untuk menyeimbangkan antara kehidupan pribadi dan pekerjaan. Keseimbangan yang terjadi di antara setiap karyawan ditinjau dari kehidupan pekerjaan dan kehidupan pribadi. Yang dimana jika setiap karyawan generasi milenial tidak dapat menyeimbangkan perannya, maka dapat menimbulkan niat untuk berhenti dari pekerjaannya. Karyawan generasi milenial yang tidak dapat menyeimbangkan waktu dan peran gandanya dapat menimbulkan turnover intention diperusahaan Agensi Bank CTBC. Penelitian ini bertujuan untuk (i) menganalisis Work Life Balance karyawan Generasi Milenial di kantor Agensi Bank CTBC (ii) untuk mengetahui Turnover Intention karyawan Generasi Milenial di kantor Agensi Bank CTBC (iii) untuk mengetahui dan menganalisis Pengaruh Work Life Balance terhadap Turnover Intention Karyawan Generasi Milenial di kantor Agensi Bank CTBC Kota Bandung. Dalam riset ini peneliti melibatkan 30 karyawan generasi milenial yang menjadi sampel penelitian. Dalam menggali data, peneliti menggunakan data primer yang meliputi kuisioner, wawancara, observasi dan juga data sekunder meliputi dokumen, buku menggunakan program IBM SPSS 25 sebagai analisis data. Adapun metode yang digunakan dalam riset ini adalah bersifat kuantitatif dengan pendekatan deskriptif verifikatif. Hasil penelitian riset ini adalah (i) Work life balance karyawan generasi milenial Agensi Bank CTBC telah dinilai baik artinya karyawan generasi milenial memiliki kemampuan yang baik dalam menyeimbangkan antara tuntutan pekerjaan dengan kebutuhan pribadi dan keluarga (ii) Turnover intention karyawan generasi milenial dalam kategori tinggi artinya karyawan generasi milenial mampu menyeimbangkan tingkat pekerjaan sehingga mengurangi keinginan dan mengurangi pikiran-pikiran untuk meninggalkan perusahaan sehingga dinilai baik (iii) Work life balance berpengaruh signifikan negative terhadap Turnover intention karyawan generasi milenial. Hasil yang didapatkan yaitu semakin tinggi work life balance yang dilakukan maka akan semakin rendah tingkat turnover intention. Sebaliknya, semakin rendah work life balance maka akan semakin tinggi tingkat turnover intention.